2020
DOI: 10.1103/physrevlett.124.043204
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Superexchange in a Tilted Mott Insulator

Abstract: In an optical lattice entropy and mass transport by first-order tunneling is much faster than spin transport via superexchange. Here we show that adding a constant force (tilt) suppresses first-order tunneling, but not spin transport, realizing new features for spin Hamiltonians. Suppression of the superfluid transition can stabilize larger systems with faster spin dynamics. For the first time in a many-body spin system, we vary superexchange rates by over a factor of 100 and tune spin-spin interactions via th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Lithium atoms can decay from excited vibrational states to lower ones by emitting Bogoliubov excitations in the superfluid bath. We note that all the different parts of our proposed process have been exper- imentally demonstrated in other works [10][11][12][13][14]. Similarly, these ingredients have been studied in a number of theory works [15,16].…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Lithium atoms can decay from excited vibrational states to lower ones by emitting Bogoliubov excitations in the superfluid bath. We note that all the different parts of our proposed process have been exper- imentally demonstrated in other works [10][11][12][13][14]. Similarly, these ingredients have been studied in a number of theory works [15,16].…”
Section: Introductionmentioning
confidence: 68%
“…The lattice is generated by interfering two counter-propagating laser beams. The tilt can be generated by using the AC stark shift from a large waist laser which is incident on the system from a direction perpendicular to the lattice [10]. The resulting potential is shown in Fig.…”
Section: B 1d Latticementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that parton gases and stripes can be realized in this setting [88]. In a setup with cold atoms in optical lattices, such a mixed dimensional system can be realized by applying a potential gradient along one direction, which inhibits tunneling of the particles but still allows for tunable spin exchange interactions along the gradient [196,41,56,190].…”
Section: Introductionmentioning
confidence: 99%
“…The description of the observed dynamics by the terms of a Floquet picture points a way to use DC driven systems [26] as opposed to AC driven systems for Floquet engineering of relevant extended Hubbard models [27]. While for AC driven Floquet systems many-body localization has been proposed for stabilization against heating, DC driven systems require Stark localization (and potentially many-body Stark localization [28]) for stabilization and our experiments show that it is promising to identify suitable regimes.…”
mentioning
confidence: 98%